Foregrounding the Disciplines for Teacher Preparation in Secondary Literacy - Conley, Mark W (Journal of adolescent & adult literacy, 2012)
Though there has been disagreement about the particular emphasis on the disciplines with literacy, there is a great deal of agreement that the disciplines matter. This article describes a course designed to prepare beginning teachers to engage in disciplinary literacy, or literacy-related ways of knowing in a discipline. After researching a topic within their discipline, considering approaches to engage students in challenging texts and contemplating ways in which students might be challenged or struggle with a set of disciplinary ideas, teacher candidates guided in decisions about literacy goals and practices. By following this sequence, beginning teachers move from an over-emphasis on pedagogy to connecting specific literacy practices to disciplinary contexts. The promise of this approach is that beginning teachers are more likely to understand relationships between disciplinary contexts and literacy and, as a result, will be more likely to sustain a focus on disciplinary literacy.